2022
DOI: 10.3390/diagnostics12030592
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of ARID1A Mutations in Endometrial Carcinomas

Abstract: Since the Cancer Genome Atlas (TCGA) project identified four distinct groups based on molecular alterations, mutation analyses have been integrated into the characterization of endometrial carcinomas (ECs). ARID1A seems to be the subunit more involved in the loss of function of the SWI/SNF complex in ECs. The aim of this study is to define the relevance of ARID1A alterations in a cohort of EC, studying the possible associations between DNA mutation (genomic level), RNA expression (transcriptomic level), and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…For this reason, misclassification of risk class corresponds to different adjuvant approaches, specifically, it may result in overtreatment or undertreatment. In a previous work by our group, we investigated the prognostic role of additional biomarkers ( ARID1A and CTNNB1 ) in endometrial carcinoma in a subset of the analyzed cohort showing the relevance of an improved surrogate molecular classification ( 10 ). In the present study, expanding the cohort analyzed, we evaluated the impact of the new ESGO/ESTRO/ESP guidelines with the incorporation of molecular subgroups of endometrial carcinoma and we compared them with the previous 2016 recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, misclassification of risk class corresponds to different adjuvant approaches, specifically, it may result in overtreatment or undertreatment. In a previous work by our group, we investigated the prognostic role of additional biomarkers ( ARID1A and CTNNB1 ) in endometrial carcinoma in a subset of the analyzed cohort showing the relevance of an improved surrogate molecular classification ( 10 ). In the present study, expanding the cohort analyzed, we evaluated the impact of the new ESGO/ESTRO/ESP guidelines with the incorporation of molecular subgroups of endometrial carcinoma and we compared them with the previous 2016 recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…We retrospectively analyzed data from the cohort of patients surgically treated at the Division of Gynecologic Oncology of “IRCCS Azienda Ospedaliero-Universitaria di Bologna” (Bologna, Italy) ( 9 ). A subset of this cohort was studied in a preliminary study on endometrial carcinoma by our group ( 10 ). The local ethics committee CE-AVEC (Comitato Etico-Area Vasta Emilia Centro) approved the present study (registration n. 27/2019/Sper/AOUBo).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ARID1A alterations in our study were found in tissue samples from virtually every type of OC; however, no alterations were detected in benign gynaecologic conditions. Typically, ARID1A loss is indicative of endometrioid-origin cancers; ARID1A mutations are found in 40% of endometrial cancers [ 27 ], 32% of endometrioid OCs, 29% of clear-cell OCs, and only 3% of HGSOC cases [ 28 ]. The De Leo et al study, which examined ARID1A mutation’s effect on transcriptomic and proteomic levels of ARID1A , in line with our study results, found no significant correlation between ARID1A mutations and mRNA expression [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Typically, ARID1A loss is indicative of endometrioid-origin cancers; ARID1A mutations are found in 40% of endometrial cancers [ 27 ], 32% of endometrioid OCs, 29% of clear-cell OCs, and only 3% of HGSOC cases [ 28 ]. The De Leo et al study, which examined ARID1A mutation’s effect on transcriptomic and proteomic levels of ARID1A , in line with our study results, found no significant correlation between ARID1A mutations and mRNA expression [ 27 ]. Although both ARID1A mutations and mRNA downregulation lacked specificity in HGSOC diagnosis, we found borderline significant associations of low ARID1A expression and reduced progression-free survival, showing the potential of ARID1A as a prognostic factor in OC.…”
Section: Discussionmentioning
confidence: 99%